Working With Others: Coping with Criticism - Marilyn K. Lesmeister (EDIS)
Whether a volunteer, community committee member, an employee, a member of a family, or a supervisor, we can cope with criticism effectively and learn from it. We can use our energy wisely to ensure a safe, productive and encouraging environment for one another, our organizations and our communities. This document is FCS9211, one of a series of the Family Youth and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 1, 2005.